Organizing villagers for self-reliance : a study of Gonoshasthya Kendra in Bangladesh - Ray, Jayanta Kumar (Calcutta : Orient Longman, 1986)
Study of public health centers in Bangladesh.
Includes bibliographycal references
Keywords: Rural development -- Bangladesh -- Savar